Proteomic study of medicinal mushroom extracts reveals antitumor mechanisms in an advanced colon cancer animal model via ribosomal biogenesis, translation, and metabolic pathways - Jakopovic, Boris; Horvatić, Anita; Baranasic, Jurica; Car, Iris; Oršolić, Nada; Jakopovich, Ivan; Sedić, Mirela; Kraljević Pavelić, Sandra (Frontiers in Pharmacology, 2024)
Colorectal cancer ranks as the third most common cancer in both men and women, with approximately 35% of cases being stage IV metastatic at diagnosis. Even with treatment advancements, the survival rates for these patients remain suboptimal. There is a significant focus on developing multi-targeted therapies due to the common issue of drug resistance in standard and targeted cancer treatments. Medicinal mushrooms, both as single compounds and as complex extracts, have undergone extensive research. Numerous types of mushrooms have been shown to be safe, effective inhibitors of cancer pathways and strong enhancers of the immune system. In this study, we performed both qualitative and quantitative proteomic analyses using tandem mass tags (TMT) on CT26 wild type (CT26.WT) colon cancer tissues from Balb/c mice, which were treated with a special blend of medicinal mushroom extracts, either alone or in combination with the chemotherapy drug 5-fluorouracil.In this study, we conducted both qualitative and quantitative proteomic analysis using tandem mass tags on CT26.WT colon cancer tissue from Balb/c mice treated with a special blend of medicinal mushroom extracts, with and without the chemotherapy agent 5-fluorouracil. The results showed a notable increase in survival rates and indicated that Agarikon Plus, both alone and combined with 5-fluorouracil or another medicinal mushroom preparation Agarikon.1, impedes multiple key processes in colorectal cancer progression. The analysis of differentially expressed proteins in treated groups was done by use of bioinformatics tools and a decrease in ribosomal biogenesis (e.g. RPS3) and translation processes (e.g. RPL14) as well as increase in unfolded protein response (e.g. DNAJC3), lipid metabolism (e.g. ACOT7), and the tricarboxylic acid cycle (e.g. FH) were observed. The treatment induced other alterations of known biomarkers and protein clusters critical to the progression and prognosis of colorectal cancer, laying a promising foundation for further translational research on this treatment modality.